THE DEVELOPMENT OF DIGITAL BOOK BASED ON A METACOGNITIVE APPROACH TO FRACTION OPERATIONS FOR CLASS V ELEMENTARY SCHOOL - Nur Rarastika; KMS. M. Amin Fauzi; Adi Sutopo (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2022)
This study aims to determine the validity, practicality, and effectiveness of learning books based on metacognitive approaches in arithmetic operations mathematics lessons. This type of research is ADDIE model development research. Data collection techniques in this study were observation, interviews, validation, and tests. This research was conducted in class V. The results showed The product was valid in terms of media by 88%, in terms of material by 93.8%, and in terms of language by 92%; The product gets a positive response from users; and The percentage of classical learning completeness reaches 85% or most of the learning outcomes are as complete as stated.